2015
DOI: 10.5796/electrochemistry.83.345
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Intercalation of Sodium Ions into Thermally Reduced Graphite Oxide

Abstract: The structure of carbon obtained from the thermal reduction of graphite oxide at 900°C after electrochemical storage sodium ions was investigated. X-ray diffraction measurement of the carbon sample after charged to various potentials indicated that sodium ions are stored between the layers of carbon below 0.3 V vs. Na/Na + though the interlayer spacing of it was similar to that of graphite. The lower LUMO energy as revealed from the broad π* peak in the region of CK observed in soft X-ray absorption measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 27 publications
2
10
0
Order By: Relevance
“…As shown on the right side of Table , GLG obtained at 700 °C (GLG700) had an interlayer distance of 0.338–0.340 nm and an oxygen content of 5.0%, as experimentally analyzed in our previous study. , These values are intermediate between K-GLG, L-GLG, and E-GLG (small), which have low oxygen content and relatively small interlayer distance, and E-GLG (large), which has high oxygen content and relatively large interlayer distance. Our previous experimental results suggested that there is not a single type of oxygen-containing functional group inside GLG, but rather that all of these groups are present. ,, Therefore, assuming an average structure for these models, their oxygen content and interlayer distance would be roughly close to the experimental values for GLG700, and the present calculations could explain the experimental values.…”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations
“…As shown on the right side of Table , GLG obtained at 700 °C (GLG700) had an interlayer distance of 0.338–0.340 nm and an oxygen content of 5.0%, as experimentally analyzed in our previous study. , These values are intermediate between K-GLG, L-GLG, and E-GLG (small), which have low oxygen content and relatively small interlayer distance, and E-GLG (large), which has high oxygen content and relatively large interlayer distance. Our previous experimental results suggested that there is not a single type of oxygen-containing functional group inside GLG, but rather that all of these groups are present. ,, Therefore, assuming an average structure for these models, their oxygen content and interlayer distance would be roughly close to the experimental values for GLG700, and the present calculations could explain the experimental values.…”
Section: Resultssupporting
confidence: 78%
“…Our previous experimental results suggested that there is not a single type of oxygen-containing functional group inside GLG, but rather that all of these groups are present. 22,23,25 Therefore, assuming an average structure for these models, their oxygen content and interlayer distance would be roughly close to the experimental values for GLG700, and the present calculations could explain the experimental values.…”
Section: ■ Computational Methodssupporting
confidence: 83%
See 2 more Smart Citations
“…The 1 H NMR spectra of both O-Pn and S-Pn dimers show the corresponding proton peaks at the aromatic region and aliphatic region. Also, 13 C{ 1 H} NMR spectra identify the corresponding carbon peaks, supporting successful preparation and purification of Pn dimers. 1-Pentanol was used as the solvent to dissolve Na metal, and the resulting NaOC 5 H 11 suspension was used to prepare S-and O-pNaPcs from their respective Pn dimers.…”
Section: Resultsmentioning
confidence: 72%